Design of Tbs Marketing Accounting Information System (Fresh Fruit Bunches) at Cv. Farmer Source - Sarima Yanti (Asosiasi Perguruan Tinggi Informatika dan Ilmu Komputer (APTIKOM) Provinsi Sumatera Utara, 2023)
Accounting Information System (AIS) is a system that aims to collect data and report information relating to financial transactions. Marketing is a total system of business activities to plan, determine prices, promote and distribute want-satisfying goods and services to both current and potential consumers. In this system an application will be designed to calculate products to be marketed and products purchased and display financial reports and journals, using the Microsoft Visual Basic 2008 programming language and the Microsoft SQL Server 2005 database. fast, and can display reports quickly, precisely and accurately.